Shattered rim and shelling of high-speed railway wheels in the very-high-cycle fatigue regime under rolling contact loading. (March 2019) - Cong, Tao; Han, Jianmin; Hong, Youshi; Domblesky, Joseph P.; Liu, Xiaolong
Abstract: Due to the improvement of the wear property, rolling contact fatigue including shattered rim and shelling are the main failure causes of the high-speed railway wheels. In this paper, shattered rim and shelling occurred on the service wheels of the China Railway High-speed (CRH) trains were systematically investigated. The recorded data of the last ten years CRH operation indicated that all shattered rims and shelling were detected with serving >10 6  km (corresponding to the fatigue life 10 7 –10 9  cycles) which is very-high-cycle fatigue (VHCF). The crack initiation region of shattered rim located at the depth of 10–25 mm from the tread, while that of shelling located at the depth <10 mm from the tread. The VHCF features under rolling contact loading were observed on the opening crack surfaces, i.e., similar VHCF features in uniaxial loading including the defect, fish-eye, and crack propagation region and unique VHCF features of the three dimensional crack surface feature, beach bands uniformly distributed in the crack propagation region, absence of fine granular area (FGA). The VHCF model considering the stress distribution, defect size and hardness were applied to discuss the failure mechanism of the shattered rim and shelling. Highlights: The shattered rim and shelling are caused by very-high-cycle fatigue (VHCF) under rolling contact loading. Unique features were presented in the crack initiation region of VHCF under rolling contact loading. The multi-axial stress distribution, the large defect, the hardness distribution are responsible for the VHCF behavior.